Resveratrol treatment reduces apoptosis and morphological alterations in cisplatin induced testis damage - ERCAN, FERİHA; ŞENER, GÖKSEL (MARMARA UNIV, 2019)
Cisplatin commonly used as a chemotheropotic agent however, it is associated with numerous side effects such as reproductive cytotoxicity. It causes spermatogenic cell death and DNA damage in spermatozoa via the formation of reactive oxygene species. Resveratrol (3,5,4'-trans-trihydroxystilbene), a natural phytoalexin, is a potent antioxidant agent, present in a wide variety of dietary sources including grapes, plums and peanuts. The aim of present study to evaluate the beneficial effects of resveratrol on cisplatin induced testis damage. Male Sprague Dawley rats were used in the study and four experimental groups were formed as: 1- saline applied control, 2- resveratrol applied control, 3- cisplatin and 4- cisplatin+resveratrol groups. Following a single dose of cisplatin (7 mg/kg i.p.), either saline or resveratrol (10 mg/kg, orally) was administered for 5 days. Testis samples were prepared for histopathological and ultrastructural evaluations, cell proliferation and apoptosis. Tissue malondialdehyde (MDA), glutathione (GSH) levels and myeloperoxidase (MPO) activity were determined biochemically. Degenerated and atrophic tubules of tissue, apoptotic cells, MDA level and MPO activity were increased although proliferation index and GSH level were decreased in cisplatin group. Degenerated tight junctions between the Sertoli cells and vacuole formation in germinal epithelial cells were also revealed at this group. However, resveratrol treatment reduced degenerated and atrophic tubules, apoptotic cells, vacuole formation in germinal epithelial cells, MDA level and MPO activity and increased proliferation index and GSH level in testis. These results showed that resveratrol ameliorates cisplatin induced testis injury by the impairment of oxidative stress and apoptosis.
Keywords: Cisplatin; resveratrol; testis; apoptosis; cell proliferation; ultrastructure; INDUCED TESTICULAR DAMAGE; INDUCED CARDIOTOXICITY; INDUCED TOXICITY; L-CARNITINE; RATS; BLEOMYCIN; ETOPOSIDE; MELATONIN; KIDNEY; INJURY